Dual-band MIMO antenna for wideband THz communication in future 6G applications - Jamal Hossain Nirob; Kamal Hossain Nahin; Md. Ashraful Haque; Md. Sharif Ahammed; Narinderjit Singh Sawaran Singh; Redwan A. Ananta; Md. Kawsar Ahmed; Liton Chandra Paul (Universitas Ahmad Dahlan, 2025)
This paper presents an industrial and innovation dual-band multiple-input multiple-output (MIMO) antenna designed for terahertz (THz) frequencies to enhance future sixth-generation (6G) communication systems. The antenna utilizes a polyimide substrate with a thickness of 12 µm, a dielectric constant of 3.5 and a tangent loss of 0.0027. Both the patch and the ground plane are constructed from copper, ensuring robust performance. The antenna achieves resonance at 5.45 THz with a gain of 14 dB and a bandwidth of 0.7 THz and at 6.34 THz with a gain of 14.44 dB and a bandwidth of 1.77 THz. Additionally, it demonstrates a minor peak at 7.4 THz and a maximum efficiency of 95.87%. The transmission coefficient shows an isolation of -31.01 dB, indicating excellent separation between antenna elements. Key MIMO performance metrics, containing the envelope correlation coefficient (ECC), diversity gain (DG), mean effective gain (MEG), total active reflection coefficient (TARC), and channel capacity loss (CCL), were analyzed, displaying optimum performance. An analogous circuit was designed and simulated in advanced design system (ADS) to validate these discoveries, creating comparable reflection coefficients to those attained from computer simulation technology (CST) simulations. These findings approve the antenna’s possible for THz-band 6G wireless communication applications.